BREX is a novel phage resistance system widespread in microbial genomes. (1st December 2014) - Goldfarb, Tamara; Sberro, Hila; Weinstock, Eyal; Cohen, Ofir; Doron, Shany; Charpak‐Amikam, Yoav; Afik, Shaked; Ofir, Gal; Sorek, Rotem
Abstract The perpetual arms race between bacteria and phage has resulted in the evolution of efficient resistance systems that protect bacteria from phage infection. Such systems, which include the CRISPR‐Cas and restriction‐modification systems, have proven to be invaluable in the biotechnology and dairy industries. Here, we report on a six‐gene cassette in Bacillus cereus which, when integrated into the Bacillus subtilis genome, confers resistance to a broad range of phages, including both virulent and temperate ones. This cassette includes a putative Lon‐like protease, an alkaline phosphatase domain protein, a putative RNA‐binding protein, a DNA methylase, an ATPase‐domain protein, and a protein of unknown function. We denote this novel defense system BREX (Bacteriophage Exclusion) and show that it allows phage adsorption but blocks phage DNA replication. Furthermore, our results suggest that methylation on non‐palindromic TAGGAG motifs in the bacterial genome guides self/non‐self discrimination and is essential for the defensive function of the BREX system. However, unlike restriction‐modification systems, phage DNA does not appear to be cleaved or degraded by BREX, suggesting a novel mechanism of defense. Pan genomic analysis revealed that BREX and BREX‐like systems, including the distantly related Pgl system described in Streptomyces coelicolor, are widely distributed in ~10% of all sequenced microbial genomes and can be divided into six coherent subtypes in which the gene composition and order is conserved. Finally, we detected a phage family that evades the BREX defense, implying that anti‐BREX mechanisms may have evolved in some phages as part of their arms race with bacteria.